2014
DOI: 10.1007/s10072-014-1813-6
|View full text |Cite
|
Sign up to set email alerts
|

Mild hypothermia alleviates excessive autophagy and mitophagy in a rat model of asphyxial cardiac arrest

Abstract: Mild hypothermia is an effective therapeutic strategy to improve poor neurological outcomes in patients following cardiac arrest (CA). However, the underlying mechanism remains unclear. The aim of the study was to evaluate the effect of mild hypothermia on intracellular autophagy and mitophagy in hippocampal neurons in a rat model of CA. CA was induced in Sprague-Dawley (SD) rats by asphyxia for 5 min. After successful resuscitation, the surviving rats were randomly divided into two groups, the normothermia (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…They were provided food and water ad libitum, and housed at 25˚C, with freshly ventilator delivered atmosphere and a 12 h light/dark cycle. The procedure of animal CA and CPR were performed as described previously (4). Endotracheal intubation was performed prior to left/right femoral arteriovenous catheterization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were provided food and water ad libitum, and housed at 25˚C, with freshly ventilator delivered atmosphere and a 12 h light/dark cycle. The procedure of animal CA and CPR were performed as described previously (4). Endotracheal intubation was performed prior to left/right femoral arteriovenous catheterization.…”
Section: Methodsmentioning
confidence: 99%
“…The principal pathological cause of organ damage is excessive apoptosis and autophagy (4,5), the extent of which has been found to correlate with poor neurological prognosis (6)(7)(8). A number of studies have demonstrated that hypothermia can attenuate neurological damage following I/R injury by reducing neural apoptosis and preventing autophagy overactivation (4,9,10). Therefore, it has been recommended as a potential treatment in patients who were successfully resuscitated following CA (11).…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, the duration of HT treatment was 4 hours, which may be contrasted with clinical use of HT. The duration of HT treatment used in this study was similar to previous studies investigating the beneficial effect of HT in a cardiac arrest rat model [25,26]. Four hours of HT may not be enough to improve neurologic outcomes in cases of clinical HT, and more prolonged HT could result in diminishing beneficial effects of VPA.…”
Section: Discussionmentioning
confidence: 62%
“…Certain environmental stimuli can inhibit or promote mitophagy and alter the content of the proteins related to this phenomenon. Mild hypothermia downregulated Parkin in hippocampal neurons in a cardiac arrest model, diminishing mitophagy in the neurons, protecting mitochondria, and improving neurological function after cardiac arrest [194]. Hypoxic preconditioning induced FUNDC1-dependent activation of mitophagy and decreased I/R-induced cardiac injury [96].…”
Section: Environmental Stimulimentioning
confidence: 99%